2008
DOI: 10.1177/0040517507084283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total Surface Area and Fabric Density on the Acoustical Behavior of Needlepunched Nonwoven Fabrics

Abstract: Nonwoven fabrics are ideal materials for use as acoustical insulation products because they have high total surface. The surface area of the fabric is directly related to the denier and crosssectional shape of the fibers in the fabric. Smaller deniers yield more fibers per unit weight of the material, higher total fiber surface area and greater possibilities for a sound wave to interact with the fibers in the structure. Another important parameter is the packing density of the fibers in the nonwoven material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 5 publications
3
65
0
Order By: Relevance
“…Sound absorbent materials produced using micro-fiber fabrics as reveals that sound absorption is superior to that of conventional fabric with the same thickness or weight 5 . In the case of woven fabric, the surface area of the fabric is directly related to the denier and cross-sectional shape of the fibers in the fabric 6 . Sound absorbency of a novel knitted spacer fabric, which can be used in automotive upholstery and has the potential for greater sound absorbency than a conventional plain knitted fabric and its derivatives 7 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sound absorbent materials produced using micro-fiber fabrics as reveals that sound absorption is superior to that of conventional fabric with the same thickness or weight 5 . In the case of woven fabric, the surface area of the fabric is directly related to the denier and cross-sectional shape of the fibers in the fabric 6 . Sound absorbency of a novel knitted spacer fabric, which can be used in automotive upholstery and has the potential for greater sound absorbency than a conventional plain knitted fabric and its derivatives 7 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tascan and Vaughn investigated the acoustical insulation of perpendicular-laid nonwoven fabrics made from different polyester fibers, and stated that fabrics made from 3 denier fibers have better sound insulation than those made from 15 denier fibers. It was also found that perpendicular-laid nonwoven fabrics made from 4DG and trilobal fibers showed better sound insulation than those made from round fibers [12,13]. Klara Kalinova reported that perpendicular-laid nonwovens (perpendicularly laid fiber web) have better sound absorption performance than longitudinally laid fiber web [14].…”
Section: Introductionmentioning
confidence: 94%
“…Tascan and Vaughn (2006) study the effect of total surface area and fabric density of a needle punch nonwoven fabric on the acoustical performance. It is found that both parameters are proportional with the sound insulation obtained [6]. Kucuk and Korkmaz (2012) also study the effect of physical parameters i.e.…”
Section: Introductionmentioning
confidence: 99%